Perkembangan dan Peranan Multimedia (Internet) Berbasis Dakwah Islam - Erwan Efendi; Natasya Piliang; Yanzah Zahir (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
The spread of information and communication technology media is intended to facilitate the needs of modern society, especially religious knowledge. Networked communication media is increasingly spreading to almost all circles. Social media networks are increasingly spreading to almost all circles. Networked social media apart from being a means of communication and information, is also a benchmark for today's society's culture. The notion that